Economic Consequences Incurred by Living Kidney Donors: A Canadian Multi‐Center Prospective Study. Issue 4 (5th March 2014) - Klarenbach, S.; Gill, J. S.; Knoll, G.; Caulfield, T.; Boudville, N.; Prasad, G. V. R.; Karpinski, M.; Storsley, L.; Treleaven, D.; Arnold, J.; Cuerden, M.; Jacobs, P.; et al.
<x xml:space="preserve">Abstract</x> Some living kidney donors incur economic consequences as a result of donation; however, these costs are poorly quantified. We developed a framework to comprehensively assess economic consequences from the donor perspective including out‐of‐pocket cost, lost wages and home productivity loss. We prospectively enrolled 100 living kidney donors from seven Canadian centers between 2004 and 2008 and collected and valued economic consequences ($CAD 2008) at 3 months and 1 year after donation. Almost all (96%) donors experienced economic consequences, with 94% reporting travel costs and 47% reporting lost pay. The average and median costs of lost pay were $2144 (SD 4167) and $0 (25th–75th percentile 0, 2794), respectively. For other expenses (travel, accommodation, medication and medical), mean and median costs were $1780 (SD 2504) and $821 (25th–75th percentile 242, 2271), respectively. From the donor perspective, mean cost was $3268 (SD 4704); one‐third of donors incurred cost >$3000, and 15% >$8000. The majority of donors (83%) reported inability to perform usual household activities for an average duration of 33 days; 8% reported out‐of‐pocket costs for assistance with these activities. The economic impact of living kidney donation for some individuals is large. We advocate for programs to reimburse living donors for their legitimate costs.